ANALISIS SWOT DALAM PEMBENTUKAN KARAKTER SANTRI TANGGUH DAN MANDIRI DI PONDOK PESANTREN AZZAHRA CIBALONG TASIKMALAYA - Abdullah , Asep; Badriya Hisniati, Sally; Basri, Hasan; Suhartini, Andewi (Jurnal Pelita Nusa, 2025)
This study aims to analysed the strengths, weaknesses, opportunities, and threats (SWOT) in the efforts of the Azzahra Cibalong Tasikmalaya Islamic Boarding School to form resilient and independent students. The research method used is qualitative with a descriptive approach, through data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the Azzahra Islamic Boarding School has strengths in the form of takhosus programs, tahfizul Qur'an, bilingual learning (Arabic-English), and social activities that support the formation of student independence. However, there are weaknesses such as limited infrastructure, consistent absence of educators, and lack of characteristics of pesantren compared to similar institutions. In terms of opportunities, pesantren gain the support of the community and religious organizations, as well as a strategic geographical position. The threat faced is the high competition between Islamic boarding schools in the Tasikmalaya area. Overall, this SWOT analysis-based strategy is an important foothold in the development of curriculum and pesantren education management to produce competitive, resilient, and independent students.